Analysis of Counseling Service Model in Covid 19 Pandemic Era: An Innovation and Implementation of Studying From Home Service - Abdul Saman; Akhmad Harum; Muhammad Ilham Bakhtiar; Muhammad Anas (Journal of Educational Science and Technology (EST), 2022)
The study aims to (1) get the description of Guidance and Counseling Services in the covid 19 pandemic era during the Studying From Home implemented by schools in South Sulawesi; (2) to identify the types of activities related to guidance and counseling services in the Covid-19 Pandemic era; and (3) to identify types of counseling service in the covid-19 pandemic era during Study From Home implemented by schools in South Sulawesi. The research method is a survey heart distributed and filled in online by 224 Guidance and Counseling Teachers in South Sulawesi teaching at the levels of Junior High School, Senior High School, and Vocational High School. Based on the discussion, it is concluded that: (1) the Guidance and counseling service during the Covid-19 pandemic in South Sulawesi was carried out online and offline, and an online Guidance and counseling service plan was provided for the Covid- 19 pandemic; (2). The  Guidance and counseling service in Covid-19 pandemic era used applications including WhatsApp and Google meet, and it was generally carried out from school rather than from home. The most frequently used applications were Zoom meetings and Google Classroom. Innovation service like school LMS was also available for guidance and counseling service. Another media was the android-based Cybercounseling because it was more practical and saved the internet data, allowed teachers and students to make short videos in TikTok as Guidance and Counseling media, and offered Guidance and Counseling room application; (3) The counseling services were generally carried out by the Guidance and Counseling teachers by making a media that an operator can control, visiting students’ homes, and giving classical and individual guidance and counseling online and offline. The home visit was the most appropriate method because it allowed teachers to identify problems faced by students and consult their parents about the learning progress of their children during learning from home during the Covid 19 pandemic.